PENGARUH PENGGUNAAN MEDIA TERHADAP KREATIF PRODUKSI BROWNIS TTV - Rosiana Andhikasari; Ferrari Lancia; Abdul Aziz (Akrab Juara : Jurnal Ilmu-ilmu Sosial, 2020)
This study is aimed to investigate the effect of media uses towards creative production of Brownis TTV on resident of Desa Sobontoro, Tulungagung, East Java. Sub variable of media uses such as frequency, intensity, duration, media content, the individual’s relationship with media. Sub variable of creative production such as continuity, composition, camera angle, punching line, gimmick, and clip hanger. Related literature used in this research is uses and gratification theory. This research belongs to quantitative research. Sample employed here is 80 resident of Desa Sobontoro, Tulungagung, East Java. In gathering the data, questionnaire is used and the result is counted by using likert scale. Moreover, to make the data valid, some tests are also used. They are validity test and reliability test. Furthermore, the data are analyzed by using double linier regression analysis. From the results of data analysis and discussion it was found that together the variables of media uses (X1) have a significant effect on creative production (Y). The contribution of these variable amounted to 45,7% of media uses, the remaining approximately influenced by other factors besides these variable. To obtain a positive perception of the public, production team of Brownis TTV must improve the quality of program television.